Metoda oceny potencjału innowacyjności i konkurencyjności przedsiębiorstwa - Pawłowski, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents chosen concepts enterprise resources structure identification and an evaluation of resources potential. The author created his own method of diagnosing enterprise innovative-ness and competitiveness potential. Within tree types of engaged capital: the intellectual, tangible and financial one, 12 subject sets have been distinguished. These sets have been analysed as reason-effect relations and forces influencing main innovative and competitive factors. The verification of the method by means of a selected empirical case confirms its usefulness in choosing forms of enterprise privatisation; it also suggests the possibility of employing the method in comparative analyses, ranking and selecting of business projects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 367-379